Architecture design of NFV PaaS platform - Binhong MAO; Zhiming YANG (Dianxin kexue)
NFV is evolving from the initial stage of software and hardware decoupling to the goal of full cloudification and cloud native,which will make the telecommunication networks more scalable,flexible and efficient.The introduction of the NFV PaaS platform is an important measure to realize the evolution and development of NFV.The basic concepts and application scenarios of NFV PaaS were introduced,several deployment options of NFV PaaS were analyzed,and an architecture design of NFV PaaS platform was proposed.The reference for telecom operators to build NFV PaaS platform will be provided.